ELECTROCHEMICAL SENSOR FOR THE DETECTION OF HYDROQUINONE USING A CARBON PASTE ELECTRODE MODIFIED WITH MOLECULARLY IMPRINTED POLY(METHYL RED) - Widianti, Riskia Chandra; Pratiwi, Yussi; Sari, Feni Mustika; Nurhaliza, Arinda Putri; Afianto, Riky; Mulyanah, Annisa; Pratiwi, Yussy (Lantanida Journal, 2025)
Tes